Feminism as Liberalism: A Tribute to the Work of Martha Nussbaum - Higgins, Tracy E. (Columbia Journal of Gender and Law, 2010)
It is a great pleasure for me to participate in this symposium organized to honor the work of Professor Martha Nussbaum. In her scholarship, Professor Nussbaum has accomplished over and over again something that is altogether too rare in the academy; she manages simultaneously to take seriously both theory and the material conditions of people’s lives, producing work that is both rigorous and relevant. Her scholarship has long informed my own both in feminist legal theory and in human rights advocacy, helping me to bridge the gap between theory and practice. For this reason, I am especially grateful for the opportunity to participate in this symposium. In this essay, I revisit and expand an argument I have made with respect to the limited usefulness of liberalism in defining an agenda for guaranteeing women’s rights and improving women’s conditions. After laying out this case, I discuss Martha Nussbaum’s capabilities approach to fundamental rights and human development and acknowledge that her approach addresses to a significant degree many of the objections I and other feminist scholars have raised. I then turn to fieldwork that I have done in South Africa on the issue of custom and women’s choices with regard to marriage and divorce. Applying Professor Nussbaum’s capabilities approach in this setting, I speculate as to the types of regulatory schemes that would be either demanded or tolerated by her approach. In the final part of the essay, I suggest that the capabilities approach offers a powerful means of specifying the preconditions for women’s exercise of autonomy within the liberal state but that it proves somewhat less useful as a guide to policy choices under conditions that fall far short of this ideal.